Pengaruh Prosentase Serat Kelapa Sawit Terhadap Umur Fatik Beban Aksial Komposit Matriks Resin - Fitri, Muhamad (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2019)
Palm Oil Industries, not only provide so many benefits, but also has a negative impact in the form of organic waste as by products of palm oil industries. Therefore, the utilization of oil palm fiber waste needs to be developed, including for structural components that retain load, through various studies in order to reduce the volume of waste caused by oil palm. One of the simplest types of load is axial load. The purpose of this study is to make polymer matrix composite materials reinforced with oil palm Â fiber, and then test the life cycle of fatigue failure axial load, of polymer matrix composite materials with several different percentages of fiber content. The material used as a matrix is YukalacÂ® 157 BTQN-EX unsaturated polyester resin (UPRs), and the catalyst uses methyl ethyl ketone peroxide (MEKPO) and Oil palm fibers as reinforcement. The content of palm oil fiber is divided into three level i.e: 3%, 5%, and 7%. The effect of the percentage content of the volume of palm oil fiber on the cycle of fatigue failure of the polymer matrix composite material were analyzed. So that later this palm matrix resin fiber composite material can really be utilized for structural components that retain load. By utilizing palm oil fiber in the production of composite materials, it is hoped that this will reduce the volume of organic waste from palm oil processing. Fatigue testing results on the percentage of palm oil fiber content of 3% obtained the shortest failure cycle life is 7.67 cycles. As for the percentage of palm oil content of 7%, the longest failure cycle was obtained to 18.33 cycles.